(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study was conducted on the aggression between Intervarsity Male and Female volleyball player from Punjab. The sample consists of 200 randomly selected athletes from different Punjab universities. The primary goal of this research is to compare the aggression of intervarsity Male and female volleyball players. The implemented questionnaire was prepared by Dr. R. L. Bharadwaj (2008) was used to obtain cognitive and physical indicators of aggression. On the basis of t-test, it is found that there is a significant difference in the aggression levels of Intervarsity Male and Female volleyball players. The significant correlation is set at 0.05